Analysis of TMJs with disc displacement computer tomography after treatment - Mirza, Р. О. (Actual Dentistry, 2024)
The aim. To define the dimensions of upper joint space during TMJ disc displacement, associated with limited mouth opening by analyzing computer tomography images. Materials and methods. 79 patients were clinically examined by means of an anamnesis collection, isometric tests, palpation of TMJ and masticatory muscles, detection of occlusal supra contacts in habitual and dynamic occlusion. For all the examined patients with permanently limited mouth opening up to 35 mm between incisors a TMJ computer tomography (CT) in habitual occlusion was performed before and after gnathological treatment. Computer tomogram images are represented by sagittal plane where dimensions of upper joint space were measured. The distance between the upper and lower central incisors was measured in millimetres at the largest mouth opening position during clinical examination. Results. For 48 (60.7%) examined patients chewing food wearing a gnathological splint was considered as an optional recommendation and was aimed at maintaining the therapeutic effect achieved during the first three months of treatment, and for 31 (39.2%) patients consuming food in a gnathological splint was a necessity for achieving physiological measurements of mouth opening, within 43-53 mm between the incisors. Conclusions. During the comparison of TMJ computer tomogram images in the closed jaws position on both sides before and after treatment of TMJ disc displacement, which is accompanied by limited mouth opening, it was found out that the maximum admissible asymmetry in articular condyle position after gnathological treatment, measured along the upper joint space was 2,8 ± 0.31 mm and was found in 11.3% of examined patients.